Procedures to investigate foodborne illness - International Association for Food Protection; SpringerLink (Online service). (New York International Association for Food Protection/Springer, 2011)
Procedures to Investigate Foodborne Illness is designed to guide public health personnel or teams in any country that investigates reports of alleged foodborne illnesses. The  manual is based on epidemiologic principles and investigative techniques that have been found effective in determining causal factors of disease incidence. The guidelines are presented in the sequence usually followed during investigations and are organized so that an investigator can easily find the information needed in any phase of an investigation. Included are descriptions of the following procedures: Plan, prepare, investigate and respond to intentional contamination of food Handle illness alerts and food-related complaints that may be related to illness Interview ill persons, those at risk, and controls Develop a case definition Collect and ship specimens and food samples Conduct hazard analysis (environmental assessments) at sites where foods responsible for outbreaks were produced, processed, or prepared Trace sources of contamination Identify factors responsible for contamination, survival of pathogenic microorganisms or toxic substances, and/or propagation of pathogens Collate and interpret collected data Report information about the outbreak This edition also contains extensively updated and more user-friendly keys to assist investigators in identifying the contributing factors that may lead to the contamination, proliferation or survival of agents of foodborne disease.
Foreword -- Introduction -- Develop a Foodborne Disease Surveillance System -- Investigate Outbreaks -- Seek Sources and Modes of Contamination and Ways By Which the Contaminants Survived and/or Proliferated -- Analyze Data -- Make Recommendations for Control -- Inform the Public -- Calculate Economic Impact of Disease Outbreaks -- Submit Report -- Use Outbreak Data for Prevention -- Addendum: Investigation of Intentional Contamination -- Further Reading -- Appendices.
Electronic reproduction.
Keywords: Foodborne diseases; Food poisoning -- Epidemiology; Food contamination -- Analysis; Electronic books